New species of Microdispidae (Acari: Heterostigmata) from alpine New Zealand - Khaustov, Alexander A.; Minor, Maria A. (Zootaxa, 2020)
Four new species of the mite family Microdispidae, Phyllodispus tenuisetus sp. nov., Promicrodispus bisetus sp. nov., Premicrodispus (Premicrodispus) novaezealandicus sp. nov., and Premicrodispus (Premicrodispulus) secundus sp. nov., are described from soil in alpine New Zealand. The genus Promicrodispus and subgenus Premicrodispus (Premicrodispulus) are recorded from New Zealand for the first time.